Factors affecting longitudinal functional decline and survival in amyotrophic lateral sclerosis patients. Issue 3 (June 2015) - Watanabe, Hazuki; Atsuta, Naoki; Nakamura, Ryoichi; Hirakawa, Akihiro; Watanabe, Hirohisa; Ito, Mizuki; Senda, Jo; Katsuno, Masahisa; Izumi, Yuishin; Morita, Mitsuya; Tomiyama, Hiroyuki; Taniguchi, Akira; et al.
Abstract Our objective was to elucidate the clinical factors affecting functional decline and survival in Japanese amyotrophic lateral sclerosis (ALS) patients. We constructed a multicenter prospective ALS cohort that included 451 sporadic ALS patients in the analysis. We longitudinally utilized the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) as the functional scale, and determined the timing of introduction of a tracheostomy for positive-pressure ventilation and death. A joint modelling approach was employed to identify prognostic factors for functional decline and survival. Age at onset was a common prognostic factor for both functional decline and survival (p < 0.001, p < 0.001, respectively). Female gender (p = 0.019) and initial symptoms, including upper limb weakness (p = 0.010), lower limb weakness (p = 0.008) or bulbar symptoms (p = 0.005), were related to early functional decline, whereas neck weakness as an initial symptom (p = 0.018), non-use of riluzole (p = 0.030) and proximal dominant muscle weakness in the upper extremities (p = 0.01) were related to a shorter survival time. A decline in the ALSFRS-R score was correlated with a shortened survival time (p < 0.001). In conclusion, the factors affecting functional decline and survival in ALS were common in part but different to some extent. This difference has not been previously well recognized but is informative in clinical practice and for conducting trials.